2019
DOI: 10.21203/rs.2.12387/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effectiveness of an interactive organ donation education intervention for Dutch lower-educated students: a cluster randomized controlled trial

Abstract: Background: Organ donation registration rates remain low, especially among people with lower educational levels. An interactive educational intervention was developed to prepare lower-educated students in the Netherlands for making a well-informed decision about organ donation. This article reports on the effects of this intervention on the intention to register (i.e. the primary outcome in the study at hand) and beliefs regarding organ donation. Methods: The effectiveness was investigated in a post-test only … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This process evaluation is part of a Cluster Randomized Controlled Trial (CRCT) evaluating the effectiveness of the organ donation program. More details about the development of the program, the study design and methods [12] and the effect evaluation [13] can be found elsewhere. The study was approved by the Ethics Committee of the Faculty of Health, Medicine and Life Sciences on 23 October 2017 (reference number: Steenaart/231017) and registered at the Dutch Trial Register (NTR6771; https://www.trialregister.nl/trial/6557).…”
Section: Methodsmentioning
confidence: 99%
“…This process evaluation is part of a Cluster Randomized Controlled Trial (CRCT) evaluating the effectiveness of the organ donation program. More details about the development of the program, the study design and methods [12] and the effect evaluation [13] can be found elsewhere. The study was approved by the Ethics Committee of the Faculty of Health, Medicine and Life Sciences on 23 October 2017 (reference number: Steenaart/231017) and registered at the Dutch Trial Register (NTR6771; https://www.trialregister.nl/trial/6557).…”
Section: Methodsmentioning
confidence: 99%